HISTOLOGI HATI IKAN BANDENG DARI TAMBAK TRADISIONAL DI KECAMATAN UJUNG PANGKAH, GRESIK - Ummul Firmani (Universitas Muhammadiyah Gresik, 2021)
Milkfish is a leading commodity in Gresik Regency, not only because of the high demand but also the high interest in cultivating milkfish as well as the distinctive taste of meat and high nutritional value. Based on interviews with milkfish farmers in Ujung Pangkah District, it is known that the productivity of the milkfish pond has decreased from year to year. The decrease in productivity in fish farming can be caused by various factors, including decreased environmental carrying capacity and water quality. The liver is one of the important organs of higher organisms including fish, which functions to detoxify and secrete chemicals used for the digestive process. The liver plays a role in metabolic processes and the transformation of pollutants from the environment. So, in this study, histological analysis of the milkfish liver was carried out, among others, the aim of which was to determine the health status of milkfish. From the analysis, it is known that the liver tissue of the milkfish in the sampling location is in an unhealthy condition due to congestion, necrosis and tissue damage or loss of connective tissue.